Cytokines as Early Markers of Colorectal Anastomotic Leakage: A Systematic Review and Meta-Analysis - Cloë L. Sparreboom; Zhouqiao Wu; Adem Dereci; Geesien S. A. Boersema; Anand G. Menon; Jiafu Ji; Gert-Jan Kleinrensink; Johan F. Lange (Gastroenterology Research and Practice)
Purpose. Colorectal anastomotic leakage (CAL) is one of the most severe complications after colorectal surgery. This meta-analysis evaluates whether systemic or peritoneal inflammatory cytokines may contribute to early detection of CAL. Methods. Systematic literature search was performed in the acknowledged medical databases according to the PRISMA guidelines to identify studies evaluating systemic and peritoneal levels of TNF, IL-1β, IL-6, and IL-10 for early detection of CAL. Means and standard deviations of systemic and peritoneal cytokine levels were extracted, respectively, for patients with and without CAL. The meta-analysis of the mean differences was carried out for each postoperative day using Review Manager. Results. Seven articles were included. The meta-analysis was performed with 5 articles evaluating peritoneal cytokine levels. Peritoneal levels of IL-6 were significantly higher in patients with CAL compared to patients without CAL on postoperative days 1, 2, and 3 (P<0.05). Similar results were found for peritoneal levels of TNF but on postoperative days 3, 4, and 5 (P<0.05). The articles regarding systemic cytokine levels did not report any significant difference accordingly. Conclusion. Increased postoperative levels of peritoneal IL-6 and TNF are significantly associated with CAL and may contribute to its early detection.